Beyond Classical Testing: A Hybrid CFA and Rasch Validation of the Comprehensive Intellectual Humility Scale in Indonesia - Lubis, Syahid Izharuddin; Deviana, Tina (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Abstract: Intellectual humility is a vital construct for fostering open-mindedness, yet its measurement often lacks cross-cultural precision. This study provides a rigorous psychometric evaluation of the Comprehensive Intellectual Humility Scale (CIHS) within the Indonesian context (N=418), employing a dual-framework approach: Confirmatory Factor Analysis (CFA) and Rasch Modeling. CFA results confirmed a robust four-factor structure with high internal consistency across all dimensions. Rasch analysis further validated the scale’s unidimensionality and person-item reliability. Notably, Wright Map analysis revealed an alignment gap, where several items were too easily endorsed, suggesting a potential ceiling effect in the Indonesian population. By integrating Classical Test Theory and Item Response Theory, this study establishes the CIHS as a high-precision tool for local research while highlighting specific areas for item recalibration to enhance measurement sensitivity. Keywords: Confirmatory Factor Analysis, Comprehensive Intellectual Humility Scale, Intellectual Humility, Psychometric Properties, Rasch Model